2011
DOI: 10.2503/jjshs1.80.19
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Initiation Timing of Drought Stress on Carbohydrate Content and Vegetative Growth in Japanese Apricot (Prunus mume Sieb. et Zucc.) ‘Nanko’

Abstract: The effects of initiation timing of drought stress on the carbohydrate content and growth of Japanese apricot (Prunus mume Sieb. et Zucc.) 'Nanko' tree were investigated. Three-year-old trees were subjected to drought stress for three months in May ('Spring') and August ('Summer'), respectively. Irrigation was started immediately after drought stress treatment had finished. The starch concentration in the roots of stressed trees increased in both 'Spring' and 'Summer' two months after starting drought stress t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…6). Our previous study showed that physiological fruit drop in the beginning of May occurs as a result of severe competition between shoot and fruits for currently synthesized carbohydrates (Tsuchida et al, 2011a) and that drought stress around May strongly inhibits vegetative growth (Tsuchida et al, 2011b). These findings confirm that growth of new organs above ground in May of the following year depends on currently assimilated rather than reserve carbohydrates.…”
Section: Discussionsupporting
confidence: 61%
“…6). Our previous study showed that physiological fruit drop in the beginning of May occurs as a result of severe competition between shoot and fruits for currently synthesized carbohydrates (Tsuchida et al, 2011a) and that drought stress around May strongly inhibits vegetative growth (Tsuchida et al, 2011b). These findings confirm that growth of new organs above ground in May of the following year depends on currently assimilated rather than reserve carbohydrates.…”
Section: Discussionsupporting
confidence: 61%
“…Previous reports clarified that water stress reduces the 13 C translocation rate in the shoots of pear trees (Teng et al, 1999) and the satsuma mandarin (Yakushiji and Morinaga, 1998), and that drought stress inhibits the accumulation of carbohydrates in the branches and roots of the Japanese apricot tree (Tsuchida et al, 2011). In the present experiment, the 13 C concentration in the twigs, fine roots, middle roots, and large roots of the drought-stressed trees at 34°C was low (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…This result can be attributed to the short period (2 months) of stress application. Tsuchida et al (2011) demonstrated that the dry weight of Japanese apricot trees declined over approximately a 3-month period of drought stress; therefore, a period of drought stress longer than 2 months is likely to cause visible tree growth inhibition. However, in this investigation, root 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…showed drought stress damaged not only shoot and fruit growth but also reduced reserve starch in the tree that will be used for the resumption of the next spring (Tsuchida et al, 2011). In Japanese pear, drought tolerance is also one of the most important characters for productivity of fruit.…”
Section: ) Research On Drought Tolerancementioning
confidence: 99%